Relationship Between Infiltration of CD163+ TAMs, FoxP3+ Tregs, or CD66b+ TANs and Cell Differentiation in Colorectal Cancer Tissues - Xiaobo Wang; Yongyu Bai; Zhuha Zhou; Bailiang Ye; Zhejing Chen; Xiaolei Chen; Wenyi Wu (Turkish Journal of Gastroenterology, 2023)
Background/Aims: There are many studies on immune cell infiltration in colorectal cancer, including FoxP3+-regulatory T cells, CD66b+ tumor-associated neutrophils, and CD163+ tumor-associated macrophages. These studies mainly focus on the relationship between cell infiltration and tumor progression, prognosis, and so on, while the relationship between tumor cell differentiation and cell infiltration is poorly understood. We aimed to explore the relationship between cell infiltration and tumor cell differentiation. Materials and Methods: The tissue microarray and immunohistochemistry were used to determine the infiltration of FoxP3+-regulatory T cells, CD66b+ tumor-associated neutrophils, and CD163+ tumor-associated macrophages in 673 colorectal cancer samples from the Second Affiliated Hospital, Wenzhou Medical University (2001-2009). Kruskal–Wallis test was used to assess the positive cell infiltration in colorectal cancer tissues with tumor cells of varying degrees of differentiation. Results: The number of CD163+ tumor-associated macrophages, FoxP3+-regulatory T cells, and CD66b+ tumor-associated neutrophils in colorectal cancer tissues was different, and the level of CD163+ tumor-associated macrophages was the highest while the level of FoxP3+-regulatory T cells was the least. There were significant differences in the cell infiltration of colorectal cancer tissue cells with different levels of differentiation (P < .05). The highest infiltration of CD163+ tumor-associated macrophages (154.07 ± 6.95) and FoxP3+-regulatory T cells (20.14 ± 2.07) were in the poorly differentiated colorectal cancer tissues, while the higher infiltration of CD66b+ tumor-associated neutrophils was in the moderately or well-differentiated colorectal cancer tissues (36.70 ± 1.10 and 36.09 ± 1.06, respectively). Conclusion: Infiltration of CD163+ tumor-associated macrophages, FoxP3+-regulatory T cells, and CD66b+ tumor-associated neutrophils in colorectal cancer tissues may be related to the differentiation of tumor cells. Cite this article as: Wang X, Bai Y, Zhou Z, et al. Relationship between infiltration of CD163 TAMs, FoxP3+ tregs, or CD66b+ TANs and cell differentiation in colorectal cancer tissues. Turk J Gastroenterol. 2023;34(7):747-752.